EXPLORING THE PERCEPTION OF EFL UNIVERSITY STUDENTS IN PROMOTING SELF-DIRECTED LEARNING THROUGH TRAVEL WRITING - Wardatin, Fajriyah Novi; Setiawan, Slamet; Mustofa, Ali (Universitas Islam Sumatera Utara (UISU), 2022)
This research explored how EFL students perceived the implementation of self-directed learning through their process of composing travel writing. With the enhancement of the independent learning model, it had become an interesting investigation of students’ engagement in their creativity. Promoting self-directed learning through the students’ travel writing becomes one of the ultimate strategies that is potentially integrated into nowadays conditions since it addresses students to foster their learning style. This research was designed as a descriptive statistics method using self-directed learning analysis by Knowles (1975) and Garrison (1997) which was employed as the theoretical framework. A total of 17 EFL University Students who joined in creative writing class volunteered for this research to have a deep interview with comprehensive related questions through a questionnaire. Based on the creative writing class they chose; the respondents were chosen at random. The optional creative writing class, which is offered for two semesters, attracts students who are interested in improving their writing. They take several courses in the class that are focused on producing various kinds of creative writing products. The results of the study show: (i) the integration of self-directed learning in students’ travel writing encourages the improvement of student writing, (ii) there is a fostering of their cultural awareness, and (iii) a building of their autonomous learning that covers three fundamental elements of self-directed learning, including self-management, self-monitoring, and motivation. Finally, promoting self-directed learning in students’ travel writing is incorporated properly to enhance the students learning model in an effective way for nowadays learning needs.